Widespread Distribution of Highly Adapted Bradyrhizobium Species Nodulating Diverse Legumes in Africa - Jaiswal, Sanjay K.; Dakora, Felix D. (Frontiers in Microbiology, 2019)
Bradyrhizobium is a one of the most cosmopolitan and diverse bacterial group nodulating a variety of host legumes in Africa, however, the diversity and distribution of bradyrhizobial symbionts nodulating indigenous African legumes are not well understood, though needed for increased food legume production. In this review, we have shown that many African food legumes are nodulated by bradyrhizobia, with greater diversity in Southern Africa compared to other parts of Africa. From a few studies done in Africa, the known bradyrhizobia (i.e. Bradyrhizobium elkanii, Bradyrhizobium yuanmingense) along with many novel Bradyrhizobium species are the most dominant in African soils. This could be attributed to the unique edapho-climatic conditions of the contrasting environments in the continent. More studies are needed to identify the many novel bradyrhizobia resident in African soils in order to better understand the biogeography of bradyrhizobia and their potential for inoculant production.